Off-label drug use in dermatology. Issue 2 (12th March 2012) - Martin, A.; Sala, F.; Vilavella, M.; Borràs, R.; Bosch, M.; Bonafont, X.
Abstract : Background: In 2010, 1% of our pharmaceutical expenditure corresponded to off-label use, except for cytostatics. The dermatology department has increased drug costs due to the off-label use. Purpose: To assess the applications and costs of off-label drug use in dermatology. To check the therapeutic results obtained and the number of available reports. Materials and methods: The authors reviewed off-label requests from Dermatology during 2009 and 2010. The authors reviewed the reports compiled in Medline from 1997 to 2010 and classified according to reported cases number in N < 10, N between 10 and 50, N between 51 and 100, and N>100. The results were classified as effective if dermatologists achieved the therapeutic objective, partially effective if they reached the initial objective at least in 50% and ineffective when they didn't achieved the therapeutic purpose. Results: In 2009, 95 drugs were requested for an off-label use representing 404, 909 €; 7 were requests from Dermatology at a cost of 49, 218 €. In 2010, 134 drugs were requested for off-label use representing 410, 716 €; 5 were requests from Dermatology represented 117, 565 €. Conclusions: During 2010 there was an increase in the cost of off-label use in dermatology due to lenalidomide. Half of the treatments were effective, 25% partially effective and 25% ineffective. One third of the requests were supported by fewer than 10 reported cases.